Gamma-glutamyltransferase (GGT) is a predictor of NAFLD activity score for diagnosing non- alcoholic steatohepatitis (NASH) (Bangladesh Medical Journal, 2024)
Nonalcoholic fatty liver disease (NAFLD) encompasses a spectrum of conditions ranging from simple steatosis to steatohepatitis, advanced fibrosis and end stage liver disease. Despite the high prevalence and severity of hepatic illness, NAFLD remains underdiagnosed, because of few symptoms, lack of accurate laboratory markers. The study was aimed at to evaluate a bio-chemical score for diagnosing non-alcoholic steatohepatitis. A hospital based cross-sectional observational study was carried out for a period of two years from July 2013 to June 2015 in the Department of Hepatology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh.  The study was conducted among 50 patients of NAFLD attending at department of Hepatology and underwent for biochemical investigations and liver biopsy with NAFLD Activity Score (NAS). All data were presented as mean ± SD and analyzed by SPSS (version 16). Qualitative data were analyzed by Chi-square test and quantitative data were analyzed by student’s t-test. Performance of the test were assessed by sensitivity and specificity test. Statistically significant result were considered when p value < 0.05. Total patients were divided into two groups 25 were NASH and 25 were non- NASH. Mean GGT was found 73.6±48.6 U/L in NASH group and 49.9±25.4 U/L in non-NASH group. There was significant difference in the NAFLD activity score for diagnosing NASH between elevated and normal GGT (P value 0.035). Higher GGT values correlated with higher specificity. The Gamma-lutamyltransferase (GGT) has been proposed as a noninvasive and available marker for assessment of NASH.Bangladesh Med J. 2023 May; 52(2): 6-10